2012
DOI: 10.1088/1674-1056/21/12/128202
|View full text |Cite
|
Sign up to set email alerts
|

Structural and magnetic properties of LiNi 0.5 Mn 1.5 O 4 and LiNi 0.5 Mn 1.5 O 4−δ spinels: A first-principles study

Abstract: Structural and magnetic properties of LiNi 0.5 Mn 1.5 O 4 and LiNi 0.5 Mn 1.5 O 4−δ are investigated using densityfunctional theory calculations.Results indicate that nonstoichiometric LiNi 0.5 Mn 1.5 O 4−δ and stoichiometric LiNi 0.5 Mn 1.5 O 4 exhibit two different structures, i.e., the face-centred cubic (Fd-3m) and primitive, or simple, cubic (P 4 3 32) space groups, respectively. It is found that the magnetic ground state of LiNi 0.5 Mn 1.5 O 4 (P 4 3 32 and Fd-3m) is a ferrimagnetic state in which the Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…The bare bulk and the surfaces generally showed high Ni/Mn migration barriers, and consequently, no reconstruction in bare structures was rationalized. LNMO with the disordered phase (Fd-3m), i.e., Ni and Mn ions randomly occupy the octahedral 16d site in a ratio of 1:3, [34] also has empty octahedral sites named 16d. The Ti-/Ta-doped surface showed lower barrier especially for Ni ion migrating to the empty octahedral site, suggesting a reconstruction process toward rocksalt phase.…”
mentioning
confidence: 99%
“…The bare bulk and the surfaces generally showed high Ni/Mn migration barriers, and consequently, no reconstruction in bare structures was rationalized. LNMO with the disordered phase (Fd-3m), i.e., Ni and Mn ions randomly occupy the octahedral 16d site in a ratio of 1:3, [34] also has empty octahedral sites named 16d. The Ti-/Ta-doped surface showed lower barrier especially for Ni ion migrating to the empty octahedral site, suggesting a reconstruction process toward rocksalt phase.…”
mentioning
confidence: 99%
“…The LiNi 0.375 Mn 1.625 O 4 supercell, on the other hand, was modeled with a the cubic disordered Fd3¯m phase, which is known to be the most stable phase for a similar LiNi 0.5 Mn 1.5 O 4 system [38,39] and was also verified by SAED to be dominant in our as-prepared LNMO. The stoichiometric LiNi 0.375 Mn 1.625 O 4 supercell of 56 atoms considered in this work consisted of 8 Li, 3 Ni, 13 Mn and 32 O atoms.…”
Section: Resultsmentioning
confidence: 66%
“…To account for strong on-site Coulomb repulsion for the 3D electrons of the Mn and Ni atoms, the Hubbard parameter U was added to the GGA functional in the rotationally invariant approach [55], in which only the difference (U eff = U−J) between the Coulomb repulsion U and screened exchange J parameters must be specified. In the present work, we chose U eff = 4.5 eV for both Mn and Ni, as these values have been shown to produce reasonably good estimates in previous studies [36,37,38]. The calculated lattice constants and bond lengths were benchmarked thoroughly against results from previous studies and are provided in the Supplementary Materials.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, using density functional theory, professor S. Shi and his team studied the magnetic properties of LNMO with two space groups ( P 4 3 32 and Fd 3̄ m ) and demonstrated that LNMO with the Fd 3̄ m space group with O vacancies has higher electronic conductivity than LNMO with the P 4 3 32 space group. 117…”
Section: Discussionmentioning
confidence: 99%